Chitra : cities and monuments of eighteenth-century India from French archives - Lafont, Jean Marie (New Delhi ; New York : Oxford University Press, 2001)
Chiefly maps and plans by French cartographers.
Includes bibliographical references (p. 143-155) and index.
Keywords: Monuments -- India; Architecture -- India -- History